Strategi Instagram @indonesiahapusfemisida dalam Membangun Kesadaran Followers sebagai Upaya Pencegahan Femisida - Aulia Hafidz Azzahra; Martini Martini; Nova Scorviana Herminasari (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Femicide is the most extreme form of gender-based violence driven by unequal power relations through the patriarchal system. The absence of regulations and data collection on femicide cases in Indonesia encourages the importance of building public awareness. This research aims to find out how @indonesiahapusfemisida followers interpret femicide awareness and the strategies used by @indonesiahapusfemisida in building awareness as prevention. The research uses a qualitative method with a feminist perspective. Data was collected by observation, interview, and documentation. The results showed that followers understand gender-based violence that is systemic and rooted in patriarchal culture, misogyny, and sexism. The strategy of @indonesiahapusfemisida includes (1) getting to know the audience without being limited by background, (2) compiling femicide messages with a gender perspective with intersectional analysis, (3) using informative and educational methods, and (4) using digital media (Instagram), visual (infographics), and verbal (discussion).